Zespół dewocjonaliów z wykopalisk na cmentarzu przy kościele pw. św. Barbary na Starym Mieście w Częstochowie - Młodkowska-Przepiórowska, Iwona (Acta Universitatis Lodziensis. Folia Archaeologica, 2019)
In 2015, during the reconstruction of Nadrzeczna Street and Bohaterów Getta Square, in the area of the intersection with Jaskrowska Street, it was made the discovery of human bone remains. As a result of the rescue investigations undertaken, an area of approximately 550 square meters was tested. They were discovered among others relics of foundations, made of broken limestone and remains of the cemetery. The historical research showed that these foundations were relics of the St. Barbara church, around which there was a churchyard cemetery called „the cemetery outside the city” in the sources. At the remains they were found rosary beads, medallions, crosses, single glass beads, iron buttons, bronze and bone coins, hooks, buckles, pieces of cloth and textile and haberdashery ornaments. Particularly noteworthy is the collection of religious items. The collection of devotional items includes 14 exhibits. It is a diverse collection in terms of morphological and stylistic, and above all iconographic. Metal medallions and crosses were made from non-ferrous metals in casting or minting techniques. The minted medallions were made from thin badges. Glass medallions were made from two glass panes, bound in a metal frame, between which there was an image reflected on the paper. The remains of rosaries are beads, differing in terms of size, colors and shapes. Only in 9 graves it was managed to set the position of devotional items on the remains of the deceased. Most often, devotions were found at the height of clasped hands folded in the lap. Other places where devotional items are found are: around the head, around the clavicle, around the thigh – above the knees and at the feet level. The subject of images on medallions and crosses is diverse. The sets of images on the obverses and other sides are also interesting. On one picture of a glass medallion it was identified the figure of Saint Josef. The figure of St. Benedict was on two medallions. The figure of St. John the Baptist was presented on one of the most carefully made cast medallions. On its other side it was recognized St. Nicholas. On the next medal, the figure of St. Francis of Paola was identified. St. Francis of Assisi appears on a very poorly legible paper picture. On the medal lion we can see St. Wojciech. On its other side there is a figure of the Guardian Angel holding the child by a hand. Burning Hearts are presented on a cast medal, on the other side of the medal with St. Wojciech. The most popular were the medallions with images of Christ and the Virgin Mary. The Polish images of the Mother of God should be taken in account, first of all, Madonna of Jasna Góra from Częstochowa. On the medallions and crosses except the characters, there are legends – inscriptions, only in Latin, made them by majuskuła with sheriffs. Most often, the medallions were „signed” by the name of the saint. In the seventeenth and eighteenth centuries, they were gladly supplied with medallions with the patrons of good death. In determining the chronology of devotional items from the church cemetery at the church of Saint Barbara, a wide chronological framework was adopted, corresponding to the period of use of the cemetery and the church, from the 17th century to probably the beginning of the 19th century. Częstochowa was the center of worship of Our Lady of Jasna Góra. It can be assumed that most of the medallions with images of the Virgin of Częstochowa, and perhaps even all of them, were probably created in Częstochowa.